2010
DOI: 10.4049/jimmunol.1000015
|View full text |Cite
|
Sign up to set email alerts
|

IL-3 Inhibits Human Osteoclastogenesis and Bone Resorption through Downregulation of c-Fms and Diverts the Cells to Dendritic Cell Lineage

Abstract: IL-3 is an important cytokine that regulates hematopoiesis and functions as a link between the immune and the hematopoietic system. In this study, we investigated the role and mechanism of IL-3 action on human osteoclast formation and bone resorption using PBMCs. PBMCs differentiate into functional osteoclasts in the presence of M-CSF and receptor activator of NF-κB ligand as evaluated by 23c6 expression and bone resorption. We found that IL-3 dose-dependently inhibited formation of 23c6-positive osteoclasts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 58 publications
3
42
0
Order By: Relevance
“…In addition, they induce expression of MMPs, which degrade cartilage matrix, thereby aggravating the degeneration of joints (15). We have previously shown that IL-3 is a potent inhibitor of osteoclast formation and pathological bone resorption in vitro (17)(18)(19)(20), and it protects cartilage and bone damage in murine models of inflammatory arthritis (20) and collagen-induced arthritis (21). In this study, we investigated the role of IL-3 in regulation of chondrocyte function in vitro and cartilage degradation in vivo in a mouse model of human OA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, they induce expression of MMPs, which degrade cartilage matrix, thereby aggravating the degeneration of joints (15). We have previously shown that IL-3 is a potent inhibitor of osteoclast formation and pathological bone resorption in vitro (17)(18)(19)(20), and it protects cartilage and bone damage in murine models of inflammatory arthritis (20) and collagen-induced arthritis (21). In this study, we investigated the role of IL-3 in regulation of chondrocyte function in vitro and cartilage degradation in vivo in a mouse model of human OA.…”
Section: Discussionmentioning
confidence: 99%
“…The high affinity receptor for IL-3 consists of a heterodimer of IL-3-specific a-chain and a common b-chain, which is shared with GM-CSF and IL-5 (33). IL-3Ra is expressed by human hematopoietic stem cells (34), endothelial cells and monocytes (35), activated T cells (21), osteoclasts (17)(18)(19), osteoblasts, and MSCs (36). In this study, we report for the first time, to our knowledge, that both mouse and human chondrocytes express IL-3Ra at transcript and protein levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-3 directly inhibited osteoclast differentiation from human peripheral blood monocytes (Gupta et al, 2010). The addition of IL-3 greatly suppressed the expressions of c-Fms, PU.1, and c-Fos.…”
Section: Regulation Of Osteoclast Differentiation By Interleukins Thamentioning
confidence: 92%
“…IL-3 is a known potent inhibitor of mouse osteoclast formation. Very recently we have shown that IL-3 also inhibits human osteoclast formation (8). Thus, IL-3 treatment may increase the percentage of Foxp3…”
mentioning
confidence: 96%